Neuromorphic Computing Transforming Disaster Management and Resilience in Civil Engineering - Firoozi, Ali Akbar; Firoozi, Ali Asghar (SpringerBriefs in Applied Sciences and Technology, 2024)
X, 90 p. 7 illus., 6 illus. in color.